Wideband Printed Antenna Design Using a Shape Blending Algorithm - Aiting Wu; Zhonghai Zhang; Boran Guan (International Journal of Antennas and Propagation, 2017)
The shape of the tuning stub of the wide slot printed antenna is an important factor which affects the antenna’s performances. In this paper, a new design and optimization method of wideband printed slot antenna using a shape blending algorithm is presented. The proposed antenna consists of a wide rectangular slot and a tuning stub, whose profile is formed by the shape blending outcome from a pie and a diamond shape. The method is used to design an ultra-wideband antenna. The impact on the impedance bandwidth through the antenna geometry change with the different shape blending results has been investigated and analyzed. To verify the proposed design, the antenna prototype was designed, fabricated, and measured. The measured results are compared with the simulation and show good agreement.